Can the soil fauna of boreal forests recover from lead-derived stress in a shooting range area? - Selonen, Salla (Ecotoxicology (London, England), 2014)
The responses of soil faunal communities to lead (Pb) contamination in a shooting range area and the recovery of these fauna after range abandonment were studied by comparing the communities at an active shotgun shooting range, an abandoned shooting range, and a control site, locating in the same forest. Despite the similar overall Pb pellet load at the shooting ranges, reaching up to 4 kg m(-2), Pb concentrations in the top soil of the abandoned range has decreased due to the accumulation of detritus on the soil surface. As a consequence, soil animal communities were shown to recover from Pb-related disturbances by utilizing the less contaminated soil layer. Microarthropods showed the clearest signs of recovery, their numbers and community composition being close to those detected at the control site. However, in the deepest organic soil layer, the negative effects of Pb were more pronounced at the abandoned than at the active shooting range, which was detected as altered microarthropod and nematode community structures, reduced abundances of several microarthropod taxa, and the total absence of enchytraeid worms. Thus, although the accumulation of fresh litter on soil surface can promote the recovery of decomposer communities in the top soil, the gradual release of Pb from corroding pellets may pose a long-lasting risk for decomposer taxa deeper in the soil